A wearable sweat rate sensor to monitor the athletes` performance during training - Salvo, P.; Pingitore, A.; Barbini, A.; Di Francesco, F. (Science & Sports, 2018)
Objectives: We developed a wearable sensor for the real time measurement of sweat rate in localized areas of the human body. This sensor represents the first step in the development of a wearable sensor network capable to estimate the global sweat rate via an ad hoc algorithm. Such device would be used to monitor athletes` hydration status during training and improve their performances.